On currency crises and contagion - Marcel Fratzscher (European Central Bank (ECB), 2002)
This paper analyzes the role of contagion in the currency crises in emerging markets during the 1990s. It employs a non-linear Markov-switching model to conduct a systematic comparison and evaluation of three distinct causes of currency crises: contagion, weak economic fundamentals, and sunspots, i.e. unobservable shifts in agents' beliefs. Testing this model empirically through Markov-switching and panel data models reveals that contagion, i.e. a high degree of real integration and financial interdependence among countries, is a core explanation for recent emerging market crises. The model has a remarkably good predictive power for the 1997-98 Asian crisis. The findings suggest that in particular the degree of financial interdependence and also real integration among emerging markets are crucial not only in explaining past crises but also in predicting the transmission of future financial crises.
Keywords: F30; E60; E65; E44; 330